E-books diffusion and use in Spain: a socio-economic perspective - Ramos Fandiño, Guadalupe Patricia; Larrañaga Rugio, Julio (Revista General de Información y Documentación, 2012)
This paper analyses the main features of the digital book market in Spain from a socio-economic viewpoint. The main problems related to the publishing industry are also highlighted as well as the role that the ebook can play to mitigate them. The question of illegal downloads of digital contents is likewise examined together with a market forecast of the ebook during the coming years
Keywords: Electronic book; digital edition; publishing; digital reading; eBooks demand; eBooks supply.